The African National Congress' foreign policy in transition: change or continuity, 1989-1994 - Machesa, Aubrey Mpho John Refiloe (Rhodes University, Faculty of Humanities, Department of Political Studies, 1997)
But the central focus will be to explore the foreign policy transition by reflecting the theory that even though international and regional political developments had an impact on the foreign policy transition of the ANC, the internal and domestic political struggles that had evolved during the same time-frame as both the international and regional political developments also had major contributions to the foreign policy transition of the movement. Within this context, the study will also explore the preliminary contours of a post-apartheid foreign policy as perceived by the ANC as to how the country will be reintegrated into the political and economic world order.
Keywords: African National Congress -- Foreign relations